Applying generation technology to a novel software representation - Mustafa Dilshad (2008)
In today's competition in the software industry it becomes essential and necessary to implement software reuse technologies for any software project to be successful in its acceptance, quality and time constraints. The software reuse technologies are relatively stable compared to the fast changing software technologies. Generation reuse technology is an old software reuse technology which is commonly used and has become a very essential way for large software projects, time-critical projects and rapid application development.